ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PADA NOTEBOOK MEREK ACER (Studi Kasus Mahasiswa Universitas Diponegoro) - Koko Arie Bowo; Abdul Hoyyi; Moch. Abdul Hoyyi (Jurnal Gaussian, 2013)
Consumer perception about notebook product is a variated, this condition based on consumer need is referred that will exploit existing facility at a notebook. Generally, consumer buys a notebook product based on some considerations for example price, brand and product quality. If the product that the of exceed its expectation, consumer will satisfied and possibility will submit the good things about the products to others people. This research aims to analyze the factors that have an effect on purchasing decisions and consumer satisfaction on Acer notebook. Data collecting in this research use questionnaire , that was distributed to 110 students from Diponegoro University that have a Acer notebook.Technique sample uses accidental sampling method. The data obtained are then analyzed using Structural Equation Modeling (SEM). Based on research result is obtained that brand image not has an effect on to purchasing decision Acer notebook, while the product quality and price have an effect on purchasing decision Acer notebook. Despitefully also, the product quality and purchasing decision Acer notebook have an effect on consumer satisfaction. Keywords: brand image, price, quality product, purchasing decision, consumer satisfaction.